Analisis Faktor Dominan Penyebab Terjadinya Pembengkakan Biaya (Cost Overrun) Pada Proyek Konstruksi Gedung Kategori Besar Dan Menengah Di Kota Padang Tahun 2017/2018 - Taufiq Alhakim Hendri; Rian Tri komara Iriana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Construction in every sector which has been done in Padang is an effort to revamp facilities and infrastructure as Padang Citizens’ activities needs. The complexity and characteristic of a project needs a good management to avoid cost overruns. This research aims to determine the validity’s level of dominant factors which cause cost overrun. This research was conducted by spreading 40 questionnaires to contractors whose classified as to middle and major category, whether are currently carrying out the project or have completed the project construction in Padang. The obtained data is processed by using a specified statistical application program. The result showed that the dominant factor which causes cost overruns to the building construction of major category based on the questionnaire’s questions; (1) too many work’s repetitions because of poor quality reaches 85,30% (2)according to the field of coordination of human resources: lack of labor reaches 85,94% (3) according to the field of control: Job delay reaches 75,92%, meanwhile, the middle category construction shows that: (1) according to the field of implementation changing frequency reaches 86,28% (2) according to the field of resources coordinator: Lack of materials reaches 79,91% (3) according to the field of accounting coordinator from government reaches 84,34%. Keywords: Cost, Overrun cost, Dominant factor, Questioner, Respondent`s profile